Los servicios sociales en la Dirección General de la Policía. - Molero Marina, Silvia; Santamarta González, Mª Carmen; Francisco León, Mª Luisa; Hernández Santamaría, Lola; López Blanco, Balbina (Cuadernos de Trabajo Social, 1994)
Sin resumen